Cone-beam micro computed tomography dedicated to the breast. Issue 12 (December 2016) - Sarno, Antonio; Mettivier, Giovanni; Di Lillo, Francesca; Cesarelli, Mario; Bifulco, Paolo; Russo, Paolo
Highlights: A micro CT system for high resolution 3D images of the breast. The system shows a spatial resolution of 6.2 mm −1 in vertical direction and 3.8 mm −1 in radial direction. Some degree of X-ray beam spatial coherence determined weak but noticeable phase-contrast effects. The phase effects produced an edge enhancement index of 1.20 in 3D slices. A breast phantom study showed the potential of detecting soft lesions and microcalcification clusters. Abstract: We developed a scanner for micro computed tomography dedicated to the breast (BµCT) with a high resolution flat-panel detector and a microfocus X-ray tube. We evaluated the system spatial resolution via the 3D modulation transfer function (MTF). In addition to conventional absorption-based X-ray imaging, such a prototype showed capabilities for propagation-based phase-contrast and related edge enhancement effects in 3D imaging. The system limiting spatial resolution is 6.2 mm −1 (MTF at 10%) in the vertical direction and 3.8 mm −1 in the radial direction, values which compare favorably with the spatial resolution reached by mini focus breast CT scanners of other groups. The BµCT scanner was able to detect both microcalcification clusters and masses in an anthropomorphic breast phantom at a dose comparable to that of two-view mammography. The use of a breast holder is proposed in order to have 1–2 min long scan times without breast motion artifacts.